Are bivalves a source of microplastics for humans? A case study in the Brazilian markets. (August 2022) - Bom, Fabio Cavalca; Sá, Fabian
Abstract: Microplastics (MPs) are a ubiquitous contaminant worldwide, damaging the environment and human health. These particles have been identified in important seafood species, which are a possible source of contamination for humans and must be investigated. This study therefore aimed to identify the concentrations of microplastics in four important species of bivalves commercialized in Brazilian markets. The presence of microplastics was identified in all bivalves, with an average concentration of 1.64 MPs/g and 10.69 MPs/ind. We concluded that bivalves are a source of microplastics for the Brazilian population. However, further studies must evaluate other species sold in different regions of the country, estimating microplastics ingested by this population through bivalves. Finally, this contamination must be controlled by regulations such as mandatory depuration, in which can effectively minimize this problem. Highlights: First analysis of MPs in bivalves from Brazilian markets Microplastics were identified in all individuals. The average concentration was 1.64 MPs/g and 10.69 MPs/ind. Depuration techniques should be considered to reduce microplastic in bivalves.